Properties and Application of Chemical Grouting Materials for Construction Joint Leakage - Baozhi Li; Weiwei Han; Shuyin Wu; Yanyan Shi; Pan Wang; Xiaoguo Wang (Advances in Materials Science and Engineering)
This paper aims to disclose the properties of the chemical grouting materials under different conditions. Firstly, the water-soluble polyurethane (WPU) slurry, oil-soluble polyurethane (OPU) slurry, epoxy resin (EP) slurry, a slurry mixed by WPU slurry, and OPU slurry marked as (WPU + OPU) slurry were selected to test the properties. The setting time, volume shrinkage, and adhesive strength were measured under room conditions and water conditions. Then, the tunnel construction joints were simulated, and the injectability and water blocking effect were analyzed to evaluate the suitability of the different grouting slurry. In addition, the results were applied in the water leakage management of the Taihu Lake tunnel project. The test results showed that each of the four materials had its performance advantages and disadvantages and provided vital guidance for the engineering application.